Interfiks Bahasa Bintauna - Lesawengan, Jeannie (Kajian Linguistik, 2015)
Previousstudies have shown interfix rarely get studied in Indonesian languages. It maydue to the inventory and distribution of interfix are unfamiliar to Indonesianlanguage. This study aims to introduce interfix and to call attention to thestructure by applying itu in Bintauna language, a Bolaang Mongondow varian oflanguage. It investigates the nature of form, function, and meaning inBintauna’s affixed words and the distribution. The result shows that interfixin Bintauna has three forms, {-ho-}, {-titi-}, and {-ki-}. Interfix {-ho-} and {-titi-}serve derivational morphemesthat derive verbs into verbs. While interfix {-ki-} serves derivationalmorpheme that derive nouns into verbs. Interfix {-ho-} states reciprocal,{-titi-} states reflective, and {-ki-} instrumental.Keywords:interfiks, affixation, language inventories, language distribution, Bintauna.